DMZ 접경지 관광 개발의 방향성 고찰: 경기도 파주시를 중심으로 - Jun Soo Kang(강준수); Yong Chul Chang(장용철) (융합관광콘텐츠연구, 2022)
목적: 본 연구의 목적은 DMZ 관광의 추구 방향성을 토대로 접경지의 실질적 관광개발 방안뿐만 아니라 효과에 대한 구체적 논의를 수행하는 것이다. 본 연구는 DMZ 관광개발을 경직된 남북한 관계의 평화 분위기 전환과 상호교류의 전지 기지 가능성으로 파악하기 때문이다. 방법: 본 연구는 DMZ 관광개발 필요성을 제시하기 위해서 접경지에 대한 종합적인 개념을 논의했고, 파주시의 문화관광 자원에 대한 종합적인 고찰을 하였다. 그리고 본 연구는 파주시의 DMZ 관광개발이 제공할 수 있는 효과를 지역 관광자원, 접경지 특성, 그리고 관광객의 관광 욕구를 중심으로 논의하였다. 결과: DMZ 접경지의 특성은 양호한 자연생태계의 보전 상태, 지역개발의 낙후성, 그리고 다양한 규제정책들로 인해서 개발에 한계를 지니고 있다. 결론: DMZ 관광의 활성화를 위해서는 규제의 완화, ‘파주 DMZ 투어 프로그램’과 지역 문화관광자원과의 긴밀한 연계성, 그리고 민간기업 자본의 적극적 유치가 필요하다. Purpose: The purpose of this study is to conduct a detailed discussion on the effect as well as the practical tourism development plan for the border area based on the pursuit direction of DMZ tourism. This is because this study identifies the DMZ tourism development as the possibility of a transition to a peaceful atmosphere in the rigid inter-Korean relations and a base for mutual exchange. Methods: In order to suggest the necessity of DMZ tourism development, this study discussed the comprehensive concept of the border area and comprehensively considered the cultural tourism resources of Paju city. In addition, this study discussed the effects that Paju city's DMZ tourism development can provide, focusing on local tourism resources, borderline characteristics, and tourists' desire for tourism. Results: The nature of the DMZ border has limitations in development due to the good conservation status of natural ecosystems, the backwardness of regional development, and various regulatory policies. Conclusion: In order to revitalize DMZ tourism, it is necessary to relax regulations, closely link the Paju DMZ tour program with local cultural and tourism resources, and actively attract private enterprise capital. KCI Citation Count: 1